2019
DOI: 10.1016/j.redox.2018.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Mst1 deletion attenuates renal ischaemia-reperfusion injury: The role of microtubule cytoskeleton dynamics, mitochondrial fission and the GSK3β-p53 signalling pathway

Abstract: Despite extensive research that has been carried out over the past three decades in the field of renal ischaemia-reperfusion (I/R) injury, the pathogenic role of mitochondrial fission in renal I/R injury is poorly understood. The aim of our study is to investigate the molecular mechanism by which mammalian STE20-like kinase 1 (Mst1) participates in renal I/R injury through modifying mitochondrial fission, microtubule cytoskeleton dynamics, and the GSK3β-p53 signalling pathway. Our data demonstrated that geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…Mammalian STE20-like kinase 1 (MST1) is a regulator of mitochondrial fission via DRP1 phosphorylation at Ser-616 and enhancement of the F-actin assembly that induces mitochondrial injury, cytochrome c release, and mROS production, thereby promoting tubular cell apoptosis in IRI, which was attenuated by genetic deletion of Mst1 [38]. In human ischemic kidneys with IRI from cadaveric kidney transplants, the duration-dependent increase in tubular apoptosis is directly related to the release of cytochrome c from the mitochondria [39].…”
Section: Ischemia-reperfusion Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian STE20-like kinase 1 (MST1) is a regulator of mitochondrial fission via DRP1 phosphorylation at Ser-616 and enhancement of the F-actin assembly that induces mitochondrial injury, cytochrome c release, and mROS production, thereby promoting tubular cell apoptosis in IRI, which was attenuated by genetic deletion of Mst1 [38]. In human ischemic kidneys with IRI from cadaveric kidney transplants, the duration-dependent increase in tubular apoptosis is directly related to the release of cytochrome c from the mitochondria [39].…”
Section: Ischemia-reperfusion Injurymentioning
confidence: 99%
“…This, in turn, induces superoxide generation by negatively affecting mitochondrial metabolism, the efficiency of the ETC, and ATP production [47]. Cisplatin-induced nephrotoxicity is also associated with increased DRP1-mediated mitochondrial fragmentation, cytochrome c release, apoptosis of proximal tubular cells, and renal injury [38]. Furthermore, blockade of mitochondrial fission abrogated cisplatin-induced proximal tubular cell apoptosis and renal injury and improved kidney function, further attesting to the critical role of mitochondrial dynamics in AKI [35].…”
Section: Cisplatin-induced Akimentioning
confidence: 99%
“…Secondly, the present study did not determine the upstream mechanism by which elevated IcP promotes ROS overproduction in ischemic stroke. It has been found that ischemia damages mitochondria and induces ROS production (36,37). Mitophagy can eliminate damaged mitochondria, reduce ROS production and then alleviate NLRP3 inflammasome activation (38).…”
Section: Discussionmentioning
confidence: 99%
“…Dnm1/Drp1 assemble on the surface of mitochondria and drive membrane constriction and the scission of the inner and outer mitochondrial membranes in a GTP-dependent manner. The endoplasmic reticulum (ER), ER-bound inverted-formin 2 (INF2), and actin assembly at mitochondria-ER contact sites are required for mitochondrial fission [15][16][17] . An increase in phospho-Drp1 levels was detected in mitochondrial outermembrane and forms a large ring-like complex to exert fission activity in sporadic Parkinson's disease cellular models, implicating increased mitochondrial fission in the pathophysiology of Parkinson's diseases 18,19 .…”
Section: Introductionmentioning
confidence: 99%